THE USE OF SPINNING-WHEEL MEDIA TO IMPROVE THE STUDENTS’ TAJWID COMPREHENSION - Zuha Prisma; Uswatun Chasanah; Zumrotul Mukaffa (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract The background of this research is that the learning media used by teachers affect students' understanding of tajwid when reading Qur'an. Simple media that can solve this problem is a rotating wheel media containing hijaiyah letters. The purpose of this study was to determine students' understanding of tajwid by using a rotary wheel in the Al-Qur'an Hadith Subject. The research method used was quantitative with quasi-experimental research and Time-Series Design. The sampling technique used purposive sampling. Data collection was done using tests and assessment rubrics. Data were analyzed using descriptive statistical techniques and t-test. The results of this study indicated that in the cognitive and skill domains, the average value of the pretest and posttest were in a good category and improved after being treated with a rotating wheel media. The t-test results showed the sig. (2-tailed) was 0.000 < 0.05. Therefore, applying the rotary wheel media increased students' comprehension of tajwid.